2018
DOI: 10.1590/0104-6632.20180353s20170144
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Copper From a Leaching Solution of Printed Circuit Boards by Using Solvent Extraction With D2ehpa

Abstract: Global generation of waste electrical and electronic equipment (WEEE) is increasing quickly. Metals from WEEE can be recovered by using unit operations of chemical engineering. This paper describes a combined hydrometallurgical route (sulfuric oxidant leaching + solvent extraction) to recover copper from printed circuit boards (PCBs). A non-magnetic fraction from comminuted PCBs was used to perform leaching tests at 75ºC for 6 hours in an oxidizing media (sulfuric acid + hydrogen peroxide). In order to separat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…The latter does not favour the extraction reaction as per Le Chatelier's principle and thus limits the extraction yield prior to reaching an optimal pH value. This result is also supported by studies conducted by Correa et al (2018) and Pospiech et al (2004).…”
Section: Ph Effectsupporting
confidence: 84%
See 1 more Smart Citation
“…The latter does not favour the extraction reaction as per Le Chatelier's principle and thus limits the extraction yield prior to reaching an optimal pH value. This result is also supported by studies conducted by Correa et al (2018) and Pospiech et al (2004).…”
Section: Ph Effectsupporting
confidence: 84%
“…The large values of this ratio for zinc and manganese extraction could also be explained by studies conducted by Correa et al (2018). Indeed, these studies have shown an increase in the extraction efficiency of the aforementioned metal cations when it is greater than 1/1.…”
Section: Effect Of O/a Ratiomentioning
confidence: 90%
“…Aluminium(III) could be selectively extracted from the final raffinate by acidic extractants such as D2EPHA, C272 or Versatic 10. 65,104 This is because the acidity of the DES is approximately in the preferred pH range for Al(III) extraction by these extractants, while lithium(I) is extracted at much higher pH values and will therefore stay in the DES raffinate. 52,105,106 Lithium(I) could then be recovered in the next step by adding sodium carbonate in order to precipitate lithium(I) carbonate.…”
Section: Non-aqueous Solvent Extraction Process For Cobalt(ii) Recoverymentioning
confidence: 99%
“…The effect of furfuryl thioalcohol concentration on extraction of copper (II) was investigated by equilibrating aqueous solution containing 100 mg L -1 copper (II), 0.5 mol L -1 Na2SO4 at pH 5.5, phase ratio O/A = 1 [13] and shaking time is 10 minutes at room temperature. The results are presented in (Fig.…”
Section: Effect Of Furfuryl Thioalcohol Concentration On Copper (Ii) ...mentioning
confidence: 99%
“…Hydrometallurgical techniques such as wet chemical method [7], emulsion liquid membrane technology [8,9], solvent extraction [10][11][12][13][14][15][16][17] etc. have been used significantly for the recovery of copper from various leach liquors.…”
Section: Introductionmentioning
confidence: 99%